Research papers Orientational mapping of minerals in Pierre shale using X-ray diffraction tensor tomography. (2021) - Mu¨rer, Fredrik K.; Madathiparambil, Aldritt Scaria; Tekseth, Kim Robert; Michiel, Marco Di; Cerasi, Pierre; Chattopadhyaya, Basab; Breiby, Dag W.
No abstract available